COVID-19 certificate as a cutting-edge issue in changing the perception of restaurants’ visitors—Illustrations from Serbian urban centers - Gajić, Tamara; Petrović, Marko D.; Blešić, Ivana; Vukolić, Dragan; Milovanović, Ilija; Radovanović, Milan; Vuković, Darko B.; Kostić, Marija; Vuksanović, Nikola; Malinović Milićević, Slavica (Frontiers in Psychology, 2022)
As one of the first European cases of the introduction of COVID-19 certificates, the Serbian Government initiated the measure of limited working hours of restaurants for unvaccinated visitors. Due to such actions and frequent bans on working during the pandemic, many restaurants in Serbia had to lay off workers or close. At the end of October 2021, the certificate for entering restaurants and all catering facilities for all the visitors became mandatory. It is interesting to note that earlier findings suggested that some personality characteristics determine the specific behaviors during the pandemic, but there is still a small number of results related to restaurants’ visitors. This study aimed to investigate the predictive strength of the Big Five Factors (BFF) to attitudes toward visits to restaurants in Serbia during the pandemic, depending on the attitudes toward accepting COVID-19 certificates. A survey was conducted on a total sample of 953 visitors of restaurants in three major cities in Serbia. The results of hierarchical regression analysis showed that Openness and Extraversion positively predict attitudes toward visits to facilities during a pandemic, while Conscientiousness and Neuroticism were negative predictors. However, in the second step of hierarchical regression analysis, attitudes toward a COVID-19 certificate as a mediator variable significantly reduced the negative effect of Neuroticism on the attitudes toward visits. It seems that, by obtaining the certificate, the fear of unsafe stays in restaurants can be reduced, and that making decisions about (no) visiting restaurants during the pandemic does not necessarily have to be compromised by emotional lability.